Pulp and paper industry : microbiological issues in papermaking - Bajpai, P. (Pratima) (Amsterdam, Netherlands : Elsevier, 2015)
Pulp and Paper Industry: Microbiological Issues in Papermaking features in-depth and thorough coverage of microbiological issues in papermaking and their consequences and the current state of the different alternatives for prevention, treatment and control of biofilm/slime considering the impact of the actual technological changes in papermaking on the control programmes. The microbial issues in paper mill systems, chemistry of deposits on paper machines, the strategies for deposit control and methods used for the analysis of biofouling are all dealt in this book along with various growth prevention methods. The traditional use of biocides is discussed taken into account the new environmental regulations regarding their use. Finally, discusses the trends regarding the future of the microbiological control in papermaking systems.
Chapter 9 -- Future ProspectsReferences; Index
Vendor-supplied metadata.
Elsevier
Keywords: Papermaking -- Microbiology; Industrial microbiology; Paper industry; Wood-pulp industry; TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; Electronic books; Electronic books